2012
DOI: 10.1128/ec.05130-11
|View full text |Cite
|
Sign up to set email alerts
|

The Polo-Like Kinase PLKA in Aspergillus nidulans Is Not Essential but Plays Important Roles during Vegetative Growth and Development

Abstract: The Polo-like kinases (Plks) are conserved, multifunctional cell cycle regulators that are induced in many forms of cancer and play additional roles in metazoan development. We previously identified plkA in Aspergillus nidulans, the only Plk investigated in filamentous fungi to date, and partially characterized its function through overexpression. Here, we report the plkA null phenotype. Surprisingly, plkA was not essential, unlike Plks in other organisms that contain a single homologue. A subset of cells lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 75 publications
5
10
0
Order By: Relevance
“…This confirms a recent finding for PlkA [49] and suggests that these kinases negatively regulate the developmental switch from asexual to sexual reproduction. PlkA is a polo like kinase and members of this family have developmental functions in mammals, flies and worms [105][108].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms a recent finding for PlkA [49] and suggests that these kinases negatively regulate the developmental switch from asexual to sexual reproduction. PlkA is a polo like kinase and members of this family have developmental functions in mammals, flies and worms [105][108].…”
Section: Discussionsupporting
confidence: 91%
“…These color differences correlated with a dark appearance of the underside of colonies grown on minimal media at 37° (Figure 5A), conditions which promote sexual development. Further examination indicated that the aberrant colony color of the plkA (AN1560), An-gin4 (AN11101) and An-mst1 (AN5674) mutants was associated with visible morphological hallmarks of sexual development, as previously reported for plkA mutants [49]. By 4 days, wild type colonies contained large numbers of asexual conidiophores with little or no evidence of sexual development.…”
Section: Resultssupporting
confidence: 65%
“…Moreover, it has been verified that proteins highly localized on septa and conidiophores or nuclei, such as AnAXL2 (localized in conidiophores), PLKA (localized in the spindle pole body [SPB] and the nucleus), and BudA (localized in septa), may play important roles during asexual and sexual development. Consequently, defects of these proteins produce abnormal nuclear division or septum formation (61)(62)(63)(64). Thus, we hypothesize that defects caused by parA and pabA may be due to the reasons for the defects in mitosis and cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility could be that MztA might be involved in the regulation of spindle formation through interaction with specific kinases, such as the polo-like kinase PlkA. PlkA plays important roles in spindle assembly and corresponding mutants exhibit similar spindle defects to those seen in mztA mutants (Bachewich et al, 2005;Mogilevsky et al, 2012).…”
Section: Spbs Of a Nidulans Are Asymmetric And Septal Mtocs Are Structurally Different From Spbsmentioning
confidence: 99%